Penerapan Artificial Intelligence untuk Analisis Risiko Proyek Green bonds di Indonesia - Judijanto, Loso; Fawait, Aldi Bastiatul (Eastasouth Institute, 2025)
The growing need for sustainable financing has positioned Green bonds as an important instrument to fund environmentally friendly projects. However, these projects face various risks, including financial, environmental, and regulatory challenges, especially in emerging markets such as Indonesia. This study explores the application of Artificial Intelligence (AI) in mitigating these risks through qualitative research involving five interviewees from the fields of finance, environment, and technology. Using NVIVO for thematic analysis, the findings highlight the potential of AI in predictive analysis, environmental monitoring, and risk scenario simulation, while overcoming challenges such as data quality, cost, and regulatory inconsistency. This study underscores the transformative role of AI in improving transparency, efficiency, and scalability in green bond risk management, and provides recommendations to stakeholders to foster sustainable finance practices in Indonesia.